2022
DOI: 10.3390/healthcare10101838
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Risk Factor for Severe COVID-19 in Hospitalized Patients: Epidemiology and Potential Mechanisms

Abstract: SARS-CoV-2 infection is a global public health problem, causing significant morbidity and mortality. Evidence shows that obesity is a recognized risk factor for hospitalization, admission to critical care units, and the development of serious complications from COVID-19. This review analyzes the available epidemiological evidence that relates obesity to a higher risk of severity and mortality from COVID-19, examining the possible pathophysiological mechanisms that explain this phenomenon on a cellular and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It has been reported that patients with obesity are more frequently hospitalized for SARS-CoV-2 [23]. Additionally, obesity is a risk factor, regardless of other comorbidities, for the development of severe conditions and mortality in patients with COVID-19 [8]. Our results highlight that 8.4% of patients with obesity present chronic respiratory disease, and 4.5% of patients without obesity present this pathology (p = 0.001).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It has been reported that patients with obesity are more frequently hospitalized for SARS-CoV-2 [23]. Additionally, obesity is a risk factor, regardless of other comorbidities, for the development of severe conditions and mortality in patients with COVID-19 [8]. Our results highlight that 8.4% of patients with obesity present chronic respiratory disease, and 4.5% of patients without obesity present this pathology (p = 0.001).…”
Section: Discussionmentioning
confidence: 50%
“…The virus spread aggressively and quickly, infecting millions of people worldwide, and generating high mortality and morbidity [6]. In diseased patients, SARS-CoV-2 mostly infects the type II pneumocytes in lungs, but also infects proximal tubule epithelial cells in the kidney in severe cases; such cells express its receptor angiotensin-converting enzyme 2 (ACE2), facilitating viral entry [7][8][9]. Infection leads to the downregulation of ACE2, which impacts the function of angiotensin II (Ang II) and renin-angiotensin system (RAS) in a variety of tissues, including lung, heart, vasculature, and kidney, and may enable the progression of COVID-19 from mild and moderate to more severe disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is uncertain whether the raised seroprevalence in these groups represents a greater risk of SARS-CoV-2 infection. However, obese individuals are known to experience more severe COVID-19 symptoms [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…This was in disagreement with the observation of the recent Khan et al ( 22 ) study which showed a significant decrease of serum CRP levels after adjunction of Vitamin D/quercetin/curcumin combination. It would also be interesting to investigate the combinatorial effect of vitamin D3, curcumin and quercetin on overweight and obese subject who are especially at risk of a severe outcome when suffering from COVID-19 ( 32 ).…”
Section: Discussionmentioning
confidence: 99%